Comparative efficacy of pregabalin and baclofen in the rodent chronic constriction injury model of neuropathic pain - Kohli, Saurabh; Sharma, Taruna; Kalra, Juhi; Dhasmana, Dilip C. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Neuropathic pain is associated with prolonged disability and is usually not responsive to conventional analgesics like NSAIDs and opioids. Even the recommended first-line drugs are effective in less than 50% patients. Thus, drugs with different mechanisms of action are needed. Baclofen, a GABA-B agonist has shown benefit in different types of neuropathic pains and is compared against pregabalin. Methods: The sciatic nerve was ligated in 2 groups of 6 rats each as per the chronic constriction injury model of neuropathic pain on day 0. After 14 days the effect of single doses of pregabalin (30mg/kg) and baclofen (5mg/kg) intraperitoneally were assessed over a 2 hours period. Thermal and mechanical hyperalgesia were assessed as measures of neuropathic pain by the hotplate and pin-prick method respectively. Results: Significant thermal and mechanical hyperalgesia was produced 14 days after sciatic nerve ligation in both the groups (p <0.05). Both pregabalin (p <0.001) and baclofen (p <0.01) were effective in decreasing thermal hyperalgesia throughout the two hours study period, but pregabalin was more effective as compared to baclofen (p <0.05) at 30, 60 and 120minutes. Both the drugs produced a significant decrease in mechanical hyperalgesia (p <0.01) throughout the study period. Again, pregabalin was the more effective drug (p <0.05) at all time points. Conclusions: Significant thermal and mechanical hyperalgesia was seen 14 days after sciatic nerve ligation. Both pregabalin and baclofen were effective in reversing the hyperalgesia, but pregabalin was the more effective of the two drugs at all time points.